A Study of the Relationship Between Teachers’ Perceptions Towards Leadership Capacity and Their Classroom Management Styles at Kunming Real-E Foreign Language Middle School, Yunnan, China - Xu, Jingwen; Vinitwatanakhun, Watana (Scholar: Human Sciences, 2021)
The main purpose of this study was to determine the relationship between teachers’ perceptions towards leadership capacity and their classroom management styles at Kunming Real-E Foreign Language Middle School, Yunnan, China. A total 73 full-time teachers from the selected school replied the questionnaires adopted by the researcher. The data collection tool for this study was a questionnaire divided into three parts, the researcher used High Leadership Capacity questionnaire by Lambert’s (2003) to assess teachers’ perceptions towards leadership capacity and used Classroom Management Profile (1996) to examine teachers’ classroom management style. Mean and Standard Deviations were used to analyze the teachers’ perceptions towards leadership capacity and their classroom management styles. Pearson Product Moment Coefficient of Correlation was used to test the relationship between the two variables. Results of the Pearson correlation shows there was a weak positive association between teachers’ leadership capacity and classroom management styles in the selected school, (r (73) = .486, p = .000).